A fresh look on financial decision-making from the plasticity perspective. Issue 4 (12th November 2018) - Erkut, Burak; Kaya, Tugberk; Lehmann-Waffenschmidt, Marco; Mahendru, Mandeep; Sharma, Gagan Deep; Srivastava, Achal Kumar; Srivastava, Mrinalini
Abstract : Purpose: The purpose of this paper is to propose an integrative framework bringing together results from neuroplasticity and decision-making from a neuroscience perspective with those from market plasticity, i.e. with which practices market actors shape markets. Design/methodology/approach: Provided that developments in neuroscience indicate that training the brain for orientation toward efficient decision-making processes under uncertainty is possible, an in-depth analysis can be conducted by using the integrative framework, which was set up by the authors for advancing research efforts in neuroeconomics and neurofinance on these lines. Findings: Markets have a plastic character; they can change shape and form and remain in that way thereafter. The marketers have always been causing this change to succeed in their marketing strategies and efforts. Plasticity, hitherto considered by marketing, market sociology and evolutionary economics, has a potential in financial decision-making processes, especially regarding its role in training the brain for stable financial decisions. Research limitations/implications: The theoretical approach can be incorporated for delivering an alternative representation of the knowledge processes associated with financial decisions. Practical implications: The practical approach can be used for improving the practical aspects of financial decision-making processes. Originality/value: The contribution is the first of its kind which integrates neuroscience approaches of plasticity and decision-making with the concept of market plasticity from the literature on economics and management, showing their similarities and opening a new front of discussion on how these two approaches can learn from each other to increase the explanatory power of financial decision-making processes and to gain new insights for financial decision makers on how to make more efficient financial decisions in the times of uncertainty.